Pengaruh Penerapan E-Kinerja dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan IGD pada Rumah Sakit Bhayangkara Kediri - Fito Jeffrison Tri Anggoro; Edy Suwasono; Rike Kusuma Wardhani (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This study aims to determine the effect of the application of e-performance and work discipline on employee work productivity at Bhayangkara Kediri Hospital. The research method used is a quantitative method with a descriptive approach. Data collection in this study was carried out by distributing questionnaires to hospital emergency room employees. Bhayangkara Kediri and calculated using the SPSS Version 25 application. The data analysis techniques used include Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, t-Test, F-Test, and R2 Coefficient of Determination Test. In the Validity Test, it was known that all question items (X1, X2, and Y) had a significance value of 0.000 < 0.05 so that each variable was declared valid. Then in the Reliability Test, each variable was declared reliable because it had an Aplha Cronbach's value of > 0.60. Then in the t-test, it was known that the variables of e-performance (X1) and work discipline (X2) had a significance value of 0.000 < 0.05 so that these two variables partially had a significant effect on employee work productivity. Then in Test F, it was shown that the results of the significance value were 0.000 < 0.05 which showed that the application of e-performance and work discipline had a simultaneous effect on the work productivity of employees at Bhayangkara Kediri Hospital.